The Use of Mind Mapping in Increasing the Eleventh Grade Students’ Ability in Writing Analytical Expositions Text of MAN 2 Payakumbuh - Hesty Rahmadhani; Carbiriena Solusia (Universitas Negeri Padang, 2023)
This study focuses on students ability in writing analytical exposition text in eleventh grade students of man 2 Payakumbuh. The purpose of this study is to see the students ability in writing analytical exposition text before using mind mapping technique. The researcher use quantitative technique by taking experiment method. The population of this research is all of the students of eleventh grade man 2 Payakumbuh registered in the 2023/2024 academic year with total 350 students in twelve classes. The sample of this reserach is the students of F2 as experimental group with 31 students and F4 as a control group with 31 students. This study used assessment rubic adapted from the Hamp-lyons theory.the result of this study shows that mind mapping technique is effectivein increasing students ability in writing analytical exposition text of students in Man 2 Payakumbuh.